Hubungan Tingkat Pengetahuan dengan Sikap Mengenai Perilaku Seks Bebas pada Remaja Putri di SMA Nusantara Palangka Raya - Neneng Safitri; Evy Kasanova; Nina Natalia (Jurnal Surya Medika (JSM), 2022)
Background: Adolescence is a transition from a child; it can be seen that changes in physiological structure and function accompany changes in body shape. With this transition, there is a significant change in mindset and great curiosity about new things. Especially sexual issues. Objective: To describe the relationship between the level of knowledge and attitudes regarding free sex behavior in adolescent girls at SMA Nusantara Palangka Raya. Subjects and Methods: This type of research is correlational research. The population and sample in this study were young women at SMA Nusantara, totaling 30 respondents using the Simple Random Sampling Technique. Bivariate analysis used the Spearman Rank test to analyze the relationship between the level of knowledge and attitudes regarding free sex behavior in adolescent girls. The results of this study indicate the majority of respondents know good attitudes 18 respondents (40%), knowledge of teenage attitudes is sufficient for 11 respondents (31%), and knowledge of adolescent attitudes is less than one respondent (29%). The results of the bivariate test obtained a significant value of 0.05, meaning there is a relationship between the level of knowledge and attitudes regarding free sex behavior in adolescent girls. Conclusion: The story of knowledge with good and sufficient adolescent attitudes can help reduce the problem of free sex behavior.